2018
DOI: 10.1007/s00737-018-0899-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma prolactin levels are associated with the severity of illness in drug-naive first-episode psychosis female patients

Abstract: Patients with schizophrenia frequently present hyperprolactinemia as a consequence of antipsychotic treatment. However, an increase in circulating prolactin levels has also been shown in patients without previous treatment. Our objective was to compare prolactin levels between antipsychotic-naive first-episode psychosis (AN-FEP) patients and healthy controls (HC). As part of an FEP program (Programa Asistencial Fases Iniciales de Psicosis [PAFIP]), 270 AN-FEP patients and 153 HC were eligible for this study. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…This may be the reason why the prolactin level was higher in women in our study. On the other hand, in studies comparing first episode psychosis patients who do not use antipsychotics with healthy controls and individuals at risk of psychosis, it was found that the prolactin level and hyperprolactinemia rate were higher, and that hyperprolactinemia is more common in women (Aston et al., 2010; Delgado‐Alvarado et al., 2019). These findings show that hyperprolactinemia in schizophrenia is not necessarily related to antipsychotic treatment, but can be found in patients not using medication and even in the prodromal stage.…”
Section: Discussionmentioning
confidence: 99%
“…This may be the reason why the prolactin level was higher in women in our study. On the other hand, in studies comparing first episode psychosis patients who do not use antipsychotics with healthy controls and individuals at risk of psychosis, it was found that the prolactin level and hyperprolactinemia rate were higher, and that hyperprolactinemia is more common in women (Aston et al., 2010; Delgado‐Alvarado et al., 2019). These findings show that hyperprolactinemia in schizophrenia is not necessarily related to antipsychotic treatment, but can be found in patients not using medication and even in the prodromal stage.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, anti‐psychotic medication is another key factor, well recognised for its ability to induce hyperprolactinaemia, which must be carefully monitored before and during treatment (Bo et al ., ; González‐Blanco et al ., ; Delgado‐Alvarado et al ., ). Clinically, the resultant hyperprolactinaemia is associated with gynaecomastia, galactorrhoea, menstrual dysfunction, and, in the context of skin, with the development of hirsutism and acne (Garnis‐Jones, ; Seeman, ; Bo et al ., ).…”
Section: Prolactin and Dopaminementioning
confidence: 97%
“…Prolactin inhibitors (known dopamine D2 receptor agonists) are frequently prescribed to treat medical illnesses such as hyperprolactinemia and Parkinson's disease, and have been shown to induce or exacerbate mania and psychosis outside the postpartum period in some individuals with these disorders [66][67][68]. Interestingly, increased prolactin plasma levels have also been associated with an increased severity of psychotic symptoms in a sample of women with first episode psychosis, controlling for the potentially confounding effect of long-term antipsychotic use [69]. Studies examining the role of prolactin in the occurrence of postpartum psychosis are rare.…”
Section: Hormonal Factorsmentioning
confidence: 99%